Hubungan Pola Makan dengan Pre Menstrual Syndrome pada Remaja Putri: Relationship Dietary with Pre Menstrual Syndrome in Young Women - Yanasita Mafluha; Iis Sumiyati; Anisyah Febri Pugianti (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2023)
The problems that adolescents feel have to do with menstruation. The disorder that occurs in menstruation is Pre Menstrual Syndrome (PMS). Pre menstrual syndrome is one of the most common gynecological diseases. More than half of women are undiagnosed and poorly managed. The purpose of this study was to determine the relationship between diet and pre-menstrual syndrome in young women. This type of research is analytical with a cross sectional approach. Simple random sampling data collection technique of 50 respondents. This study used primary data using questionnaires. The results of the study obtained a statistical pvalue test = 0.025 meaning that there is a relationship between diet and the incidence of pre-menstrual syndrome. It is recommended to the community, especially young women, to be given counseling on the importance of maintaining a diet to minimize the incidence of pre-menstrual syndrome.